The Influence of Muhammad Abduh in The Nusantara: From Qur’anic Exegesis to Islamic Reform Movement - Ahmad Nabil Amir (Fakultas Studi Islam dan Peradaban, Universitas Muhammadiyah Yogyakarta, 2022)
This paper aims to present a survey of Abduh's extensive influence on Islamic reform (tajdid) in the Indo-Malay Archipelago, which often called Nusantara. Muhammad Abduh had a remarkable and lasting impact on religious thought and movement in Nusantara. His works and ideas were influential in the political and social landscape. He strongly impacted the movements of Muhammadiyah, al-Irsyad, Persatuan Islam (Persis), and Sarekat Islam. His Tafsir al-Manar brought inspiration with a rational outlook that influenced major tafsir works such as Tafsir al-Azhar, Tafsir al-Quranul Karim, Tafsir al-Qur'an al-Madjied (Tafsir al-Nur), Tafsir al-Qur'an al-Hakim, Tafsir al-Misbah, and Tafsir al-Furqan. The al-Manar magazine initiated by Muhammad Abduh significantly inspired many reform-oriented works and periodicals such as journal al-Imam, al-Munir, al-Ikhwan, Saudara, al-Dhakhirah al-Islamiyah, Qalam, and Seruan Azhar.